Simultaneous Determination of Fourteen Marker Compounds in the Traditional Herbal Prescription, Geumgwesingihwan, Using Ultra-Performance Liquid Chromatography–Tandem Mass Spectrometry - Chang-Seob Seo; Mee-Young Lee (Molecules, 2022)
Geumgwesingihwan (GSH) is a traditional herbal prescription composed of eight medicinal herbs: Rehmannia glutinosa (Gaertn.) DC., Dioscorea japonica Thunb., Cornus officinalis Siebold and Zucc., Poria cocos Wolf, Paeonia suffruticosa Andrews, Alisma plantago-aquatica subsp. orientale (Sam.) Sam., Achyranthes bidentate Blume, and Plantago asiatica L. This study developed and validated an ultra-performance liquid chromatography–tandem mass spectrometry (UPLC–MS/MS) method in the multiple reaction monitoring (MRM) mode for simultaneous determination of 14 compounds (allantoin, gallic acid, 5-(hydroxymethyl)furfural, geniposidic acid, oxypaeoniflorin, loganin, geniposide, paeoniflorin, ecdysterone, verbascoside, cornuside, benzoylpaeoniflorin, paeonol, and alisol B acetate) in GSH. The chromatographic separation of all marker analytes was carried out on an Acquity UPLC BEH C18 column (100 mm × 2.1 mm, 1.7 µm) using gradient elution of a mobile phase of distilled water–acetonitrile containing 0.1% acetic acid. The newly established UPLC–MS/MS MRM method was validated by evaluating the linearity, the limits of detection and quantification, recovery, and precision. All markers were detected at concentrations of 6.94–4126.28 mg/kg. In addition, the recovery was 76.65–119.49% and the relative standard deviation value of the precision was 0.19–9.91%. The newly developed and validated UPLC–MS/MS assay will provide useful information for quality assessment of GSH.